The role of 18F-FDG PET/CT in evaluation of Primary CNS lymphoma: The path less travelled - Sharjeel Usmani; Anjali Jain; Khulood Al Riyami; Shah P Naumani; Rashid Al-Sukaiti; Muhammad Shahzad Shamim (Journal of the Pakistan Medical Association, 2023)
Primary central nervous system lymphoma (PCNSL) is a rare but highly aggressive lymphoma with increasing incidence in immunocompromised patients. MRI is the modality of choice in evaluating brain lesions. However, MRI is often challenging in the detection of early recurrence, assessing residual disease and response evaluation in PCNSL. 18F-FDG PET/CT has superior diagnostic performance compared with body CT in the evaluation of lymphoma. 18F-FDG PET-CT is helpful in evaluating evaluation of disease extent and differentiating primary CNS lymphoma from systemic lymphoma. Besides diagnostic and prognostic value in primary CNS lymphoma, it might also be helpful in response assessment. The role of FDG-PET in PCNSL is not fully defined. In this article we have reviewed the potential role of 18F-FDG PET/CT in initial diagnosis, baseline staging, restaging, evaluation of treatment response, prognostication, and survival analysis of PCNSL. Keywords: 18F-FDG PET/CT; CNS lymphoma; brain tumors.